Sosialisasi Pengembangan Generasi Muda Tentang Key Success Factors and Entrepreneurship - Imelda Sitinjak; Anne R. Malau; Hamonangan Siallagan; Manatap Berliana Lumbangaol (Jurnal Visi Pengabdian Kepada Masyarakat, 2021)
The purpose of this community service activity is to provide understanding and motivation through socialization for the younger generation of Punguan Raja Panjaitan Dohot Boruna (PRPB) Medan City, one of the topics is about the key factors of success for someone with an entrepreneurial spirit. This socialization was carried out on Friday, April 30, 2021, offline with strict health protocols at the PRPB Secretariat of Medan City which was attended by 29 people. The implementation includes the opening, the MC invites participants to sing, ice breaking, socialization, video screenings, question and answer sessions, and participant feedback. For the young generation of PRPB, this socialization is important to understand what are the key factors that influence their future success, how to explore and find them. For the Medan City PRPB organization, this socialization is an alternative for developing PRPB members and reducing children's problems that arise as a result of this misunderstanding. , they can clearly summarize the topics presented and hope that a further development program will be held, so it can be concluded that the purpose of this service has been achieved.